Effectiveness of Kelakai (Stenochlaena palustris (Burm.) Bedd) Extract as an Anti-diabetic through Increased GLUT 4 Expression without Affecting Insulin Levels - Ananda, Kiki Rizky; Muthmainah; Hikmayani, Nur Hafidha (Journal of Health Science and Medical Research, 2025)
Objective: Untreated hyperglycemia disrupts insulin secretion and blocks glucose transporter 4 (GLUT 4), consequently affecting the glucose levels of patients with type 2 diabetes mellitus. This study aimed to investigate the effectiveness of kelakai on GLUT 4 expression. Material and Methods: In this study, a laboratory experiment was performed, with a pre and posttest group design for fasting blood glucose and insulin levels and using posttest only expression GLUT 4 immunohistochemistry methods. A total of 25 rats were divided into 5 groups: nondiabetic, diabetic, diabetic+glimepiride, diabetic+kelakai extract 400 mg/kgBW, and diabetic+kelakai extract 800 mg/kgBW for 21 days. Results: The 400 and 800 mg/kgBW groups had significant effects (p-value<0.05) on decreasing the fasting glucose levels. A 400 mg/kgBW dose gave a better picture of the fasting glucose levels and reversed the GLUT 4 expression to normal levels. The kelakai extract lowered the fasting blood glucose levels by increasing the GLUT 4 expression in the soleus muscle tissue without affecting the insulin secretion. Conclusion: Kelakai (S. palustris (Burm.f) Bedd) extract significantly reduced the fasting glucose levels by increasing the GLUT 4 expression without affecting the insulin levels at the best dose of 400 mg/kgBB. Thus, it has potential for use in anti-diabetic therapy.